1951
DOI: 10.1172/jci102478
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Proteins in Toxemias of Pregnancy

Abstract: Numerous studies of the toxemias of late pregnancy have consistently demonstrated the association of pre-eclampsia and eclampsia with disturbances of protein metabolism indicated by derangements in the protein composition of the blood. Whether these changes in themselves cause the symptoms of toxemia or are secondary to the elusive "toxic" factor has not been determined. Many circumstances are known to provide the basis for protein deficiency within the human body, by increasing the tissue requirement for prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

1952
1952
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 12 publications
3
15
0
1
Order By: Relevance
“…per cent in nonpregnant adults, and 3.4 Gm. per cent in pregnancy and in the newborn (17). The basis for the use of assumed rather than measured albumin values, and other assumptions involved in the calculations are considered in the discussion.…”
Section: Methodsmentioning
confidence: 99%
“…per cent in nonpregnant adults, and 3.4 Gm. per cent in pregnancy and in the newborn (17). The basis for the use of assumed rather than measured albumin values, and other assumptions involved in the calculations are considered in the discussion.…”
Section: Methodsmentioning
confidence: 99%
“…This could not be explained solely by a diminished quantity of protein (59). Numerous studies have confirmed a loss of the serum proteins, albumin and gamma-globulin, in normal pregnancy (60)(61)(62)(63)(64). In 1970, Studd and co-workers (64-67) published a series of articles, which indicated that several proteins, in addition to albumin and gamma-globulin, are decreased in late pregnancy and more so in preeclampsia (viz., transferrin and hemopexin).…”
Section: Figurementioning
confidence: 99%
“…23 Absolute values for serum albumin and globulin are lower in toxemias than in uncomplicated pregnancies. 41 ' 93 Parviainen and coworkers 108 found all the plasma protein fractions, except fibrinogen, in the urine of patients with toxemias of pregnancy of varying severity. In mild toxemia, the percentage of albumin was lower and that of alpha globulin higher than in the plasma; in pre-eclampsia and eclampsia, the urinary albumin was higher and alpha globulin lower.…”
Section: Protein Patterns In Physiologic and Pathologic Statesmentioning
confidence: 99%